Pelatihan Akuntansi Praktek Mandiri Dokter Umum, Dokter Gigi Dan Keperawatan Di Kertosono Nganjuk Jawa Timur - Kusuma, Marhaendra; Sari, Hanifah Puspita; Marjukah, Anis; Suaidah, Yuniep Mujati; Ratih, Nur Rahmanti (Jurnal Abdi Masyarakat Nusantara, 2024)
The community service activity in the form of "Accounting Training for Independent Practice of General Practitioners, Dentists and Nursing in the Kertosono Nganjuk Area" is a collaboration of five permanent lecturers from four universities, namely Kadiri Islamic University, Widya Dharma University Klaten, STIE PGRI Dewantara Jombang and State Polytechnic Poor. This activity was attended by doctors and nurses in Kertosono who have non-BPJS Independent Practice businesses. This activity was held for two days, namely 15-16 December 2023 in the Kertosono Community Health Center meeting room at the presenters' own expense. The aim of this activity is to provide a practical understanding of the application of accounting for general practitioners, dentists and nurses who run independent business practices, and to train general practitioners , dentists and nurses prepare and interpret financial reports for independent practice businesses that are run. Keywords: Accounting; Independent Practice Doctor.